Сonsidering domestic violence as a systemic delict in the criminal law framework - Kuttygaliyeva А.Р.; Yermukhametova С.Е.; Yessengaziyeva А.К. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
This article presents a comprehensive examination of domestic and family violence through the lens of the concept of a systemic criminal delict. Traditional criminal law tends to treat acts of domestic violence as discrete, isolated offences, which fail to capture their true nature as a persistent behavioural pattern aimed at establishing control over the victim. The paper substantiates the need to move from an incident-based to a systemic approach, whereby domestic violence is conceptualised as a single, prolonged delict encompassing a range of physical, psychological, economic, and sexual abuses. Drawing upon a comparative legal analysis of the legislation of the Republic of Kazakhstan, the United Kingdom, the United States, and several European countries, as well as international standards (including the Istanbul Convention and CEDAW recommendations), the study identifies key gaps in legal regulation. It proposes an original model for the criminalisation of domestic violence as an independent systemic delict. The methodological framework is based on comparative legal, dogmatic, systemic-structural, and statistical methods. The findings demonstrate that the incident-based approach is ineffective in addressing domestic violence and that the introduction of the systemic delict concept would enable more robust criminal law protection for victims, as well as more accurate legal classification of perpetrators’ actions.